The Gain-of-Function R222S Variant in Scn11a Contributes to Visceral Hyperalgesia and Intestinal Dysmotility in Scn11aR222S/R222S Mice - Zhao, Chenyu; Jin, Jishuo; Hu, Haoye; Zhou, Xi; Shi, Xiaoliu (Frontiers in Neurology, 2022)
The SCN11A gene encodes the α-subunit of the Nav1.9 channel, which is a regulator of primary sensory neuron excitability. Nav1.9 channels play a key role in somatalgia. Humans with the gain-of-function mutation R222S in SCN11A exhibit familial episodic pain. As already known, R222S knock-in mice carrying a mutation orthologous to the human R222S variant demonstrate somatic hyperalgesia. Here, we show that Scn11aR222S/R222S mice develop visceral hyperalgesia and intestinal dysmotility. Visceralgia was tested using the abdominal withdrawal reflex, acetic acid-induced writhing and formalin-induced visceral nociception tests. Intestinal motility was detected by mechanical recording of the intestinal segment, and a carbon powder propelling test. Gut neurotransmitters participate in regulating intestinal motility and secretory function. The excitability of the enteric nervous system could influence gut neurotransmitters. Vasoactive intestinal peptide and substance P were measured in intestinal tissues. Scn11aR222S/R222S mice showed lower visceralgia thresholds and slowed intestinal movements compared with wild-type controls. Lower substance P and vasoactive intestinal peptide concentrations in Scn11aR222S/R222S mice indicated less intestinal smooth muscle contraction and less intestine secretion respectively. Therefore, the SCN11A gene participates in visceral hyperalgesia and intestinal dysmotility.